Acellular Bovine Pericardial Patch for Difficult Abdominal Closure in the Pediatric Population: Our Experience with Review of Literature - Debalina Karmakar; Kalyani Saha Basu; Syamantak Basu; Saikat Chakrabarty; Koushik Saha; Dipak Ghosh (Wolters Kluwer Medknow Publications, 2024)
Aims: Closure of congenital body wall defects in children can be a challenging task for the pediatric Surgeon. Biological prosthesis has been increasingly used for high-risk wound closure in adult patients with excellent outcomes and use in the pediatric population has also been reported. Here, we aim to study the outcome of abdominal wound repair with a tissue-engineered acellular bovine pericardial patch. Methods: Over a period of 21 months, a total of 15 children had undergone abdominal wound repair with bioprostheses, i.e., bovine pericardial patch at our institute. Patient demographics, cause of defect, an indication of patch use, rate of infection, postoperative recovery, recurrence, and outcome were studied. Results: A total of 15 patients underwent abdominal wall closure with acellular bovine pericardial patch. Nine out of 15 patients were neonates, of whom five had gastroschisis, two had a congenital diaphragmatic hernia, and two had ruptured omphalocele major. Of the rest 6 patients, 2 were patients of bladder exstrophy, 2 were older children of congenital diaphragmatic hernia with incisional hernias, and 2 were older children with omphalocele major. Out of the five patients with gastroschisis, two died during the early postoperative period due to sepsis. The wound healed in the rest 13 patients with mild skin dehiscence in two patients. Only one child had a recurrence. Conclusion: Reconstruction with acellular bovine pericardial patch is a viable option in children with high-risk abdominal wounds as it allows tensionless repair with excellent healing and minimal complications. Recurrence, if any, may disappear with time as remodeling of the prosthesis occurs along with the growth of the body wall of the child.